The relationships between the mental health of elementary school students and the practices and parenting styles - Barboza Cid, Maria Fernanda; Simões Matsukura, Thelma; Cia, Fabiana (O Mundo da Saúde, 2015)
Objectives: This study aimed to relate to children’s mental health of school children of the first cycle of basic education with parenting practices and styles of those responsible. Methods: This study included a total of 321 first- to fifth-grade children and their parents or guardians. The measurement instruments used for data collection were the strengths and dif- ficulties questionnaire, the parenting styles inventory and the activities of daily life questionnaire. Correlation analyses and comparative analyses were performed. Results: The results indicated significant correlations between parenting practices and child mental health. This study also suggested that in families where boundaries, rules and roles were established, including shared responsibilities, they have been shown to be associated with higher rates of child pro-social behavior, indicating protective factors for the mental health outcomes of children. Conclusions: The study revealed that there are links between child mental health, and the parenting practices and styles adopted by those responsible in order that the more positive practices, the fewer difficulties in mental health children present. It is believed that the results may contribute towards subsidizing relevant issues to be considered by public policies of child mental health.